Nanosecond Pulsed Electric Fields (nsPEFs) Induce Socs1 and Socs3 but not Socs2 Gene Expressions in Hela S3 Cells - Rohmah, Martina Kurnia; Lyrawati, Diana; Yano, Kenichi (Fakultas Kedokteran Universitas Brawijaya, 2015)
Nanosecond Pulsed Electric Fields (nsPEFs) is one of bioelectric technologies applied widely in a number of sciences. nsPEFs cause some biological responses and known to play a role as a novel cancer therapy. However, the nsPEFs molecular mechanisms have not been fully elucidated. This study determines the effects of nsPEFs in socs (Suppressor of Cytokine Signaling) genes which are target genes of JAK/STAT signaling pathway. Through a negative feedback mechanism, SOCS proteins can suppress both cytokine signal transduction and overgrowth factor, so the cell growth is controlled. In cervix cancer, the presence of E6 and E7 HPV's oncoprotein is associated with methylation and inactivation of socs1 and socs3 genes. This mechanism is related to the increase of STAT expression and cancer prognostic. In this research, nsPEFs as much as 20 kV/cm for 80 ns was exposed over HeLa S3 cells in 4 mm cuvette. Socs1, socs2 and socs3 gene expressions were analyzed using real time PCR SYBR green and reverse transcription PCR (RT-PCR). This study shows that at 20 and 30 shots, nsPEFs significantly increase socs1 and socs3 but not socs2 gene expression. Effect of nsPEFs on socs1 and socs3 gene expression pattern is influenced by duration of post exposure incubation and each cell activity on internal cell condition. This research provides a new cancer therapy target for nsPEFs.Keywords: Bioelectric, gene expression, nsPEFs, shot, socs gene